Monitoring spatial and temporal soundscape features within ecologically significant U.S. National Marine Sanctuaries. Issue 8 (5th September 2021) - Stanley, Jenni A.; Van Parijs, Sofie M.; Davis, Genevieve E.; Sullivan, Megan; Hatch, Leila T.
Abstract: The U.S. National Oceanic and Atmospheric Administration's Office of National Marine Sanctuaries manages a system of marine protected areas encompassing more than 2, 000, 000 km 2 . U.S. National Marine Sanctuaries (NMS) have been designated to provide protection for their conservation, recreational, ecological, historical, scientific, cultural, archaeological, educational, or aesthetic qualities. Due to the large variability of attributes among NMS, designing coordinated system‐wide monitoring to support diverse resource protection goals can be challenging. Underwater sound monitoring is seeing increasing application to marine protected area management because it is able to support this wide variety of information needs. Passive acoustics are providing invaluable autonomous information regarding habitat associations, identifying species spatial and temporal use, and highlighting patterns in conditions that are otherwise difficult to survey. Using standardized equipment and analysis methods this study collected ambient underwater sound data and derived measurements to investigate temporal changes in sound pressure levels and power spectral density, identify presence of select species of importance and support within and among site comparison of ambient underwater sound among eight sites within four U.S. NMS. Broadband sound pressure levels of ambient sound (10–24, 000 Hz) varied as much as 24 dB re 1 µPa (max difference 100–124 dB re 1 µPa) among the recording sites, sanctuaries, and seasons. Biotic signals, such as snapping shrimp snaps and vocalizations of fishes, exhibited distinct diel and seasonal patterns and showed variation among sites. Presence of anthropogenic signals, such as vessel passage, also varied substantially among sites, ranging from on average 1.6–21.8 h/d. The study identified measurements that effectively summarized baseline soundscape attributes and prioritized future opportunities for integrating non‐acoustic and acoustic variables in order to inform area‐specific management questions within four ecologically varying U.S. National Marine Sanctuaries.